The Role of Indigenous Taboos and Superstitions in the Conservation of Fisheries Resources in Nigeria: A Review - Reuben Laraba Love; Mohammed Abubakar Mohammed (Journal of Multidisciplinary Science: MIKAILALSYS, 2025)
This study investigates the role of indigenous taboos and superstitions in the conservation of fisheries resources in Nigeria's diverse aquatic habitats, which are now threatened by pollution, climate change, and overfishing. The study explores the lack of use of dwelling communities’ ecological knowledge, including various fish-related taboos, examining what they mean in practice, why they exist, and the problems they encounter today. Through a qualitative literature review and case study analysis, the research reveals that indigenous taboos, categorized as species-specific, habitat-related, spatial, and methodological, significantly support fish stock preservation, habitat conservation, and ecological integrity. These taboos include no-fishing zones and seasonal restrictions. However, traditional systems face several challenges due to the weakening of traditional institutions, religious changes, economic pressures, and external influences. To be more effective, fishery management systems should be integrated with cultural conservation training and scientific testing of local practices to enhance the sustainability of Nigeria's fishery resources.